Dyskinetic vs Spastic Cerebral Palsy: A Cross-sectional Study Comparing Functional Profiles, Comorbidities, and Brain Imaging Patterns. (August 2018) - Reid, Susan M.; Meehan, Elaine M.; Reddihough, Dinah S.; Harvey, Adrienne R.
The authors aimed to describe the distribution of predominant and secondary motor types and compare functional profiles, comorbidities, and brain imaging patterns between dyskinetic and spastic cerebral palsy. Children recruited from a cerebral palsy register were assessed at age 5, 10, or 15. Motor types, topography, functional classifications, and comorbidities were recorded. Univariable logistic regression was used to compare dyskinesia with spasticity, with and without adjustment for topography. Neuroimaging classifications were extracted from the register. Of 243 children with spasticity or dyskinesia, the predominant motor type was spastic in 183 and dyskinetic in 56. Dyskinesia was associated with comparatively poorer function, total body involvement, and gray matter injury. After adjustment for topography, dyskinesia was associated with similar or better function. The study suggests that practical tools routinely incorporated into clinical practice would facilitate accurate and reliable classification of predominant and secondary motor types, topography, and functional abilities.